High-dose chemotherapy for germ cell tumors: do we have a model?. (January 2015) - Necchi, Andrea; Lanza, Francesco; Rosti, Giovanni; Martino, Massimo; Farè, Elena; Pedrazzoli, Paolo
<x xml:space="preserve">Abstract</x> Introduction: Since the late nineties, the intensification of chemotherapy doses with hematopoietic stem cell rescue held promise for patients with advanced and poor prognosis germ cell tumors (GCTs). High-dose chemotherapy (HDCT) has, nowadays, a recognized indication in the salvage setting of advanced GCTs and is steadily utilized worldwide. Areas covered: We evaluated the available data with the use of HDCT in these patients. In addition, we provided an original perspective on several issues as experts on behalf of the European Society for Blood and Marrow Transplantation and IGG, including peripheral blood stem cells mobilization and the use of HDCT in special subpopulations of GCT, with the aim to help clarify critical issues in the absence of available clear-cut information. Expert opinion: Despite HDCT being currently considered a therapeutic option in the salvage setting, critical questions regarding patient selection are still unanswered. Eligibility of patients with a chemoresistant disease, the use of available prognostic factors as well as tumor marker decline in clinical practice are pending issues. Moving forward, these are critical arguments in favor of further clinical research in the field of advanced GCTs.